Surface circulation and temperature distribution of Southern South China Sea from Global Ocean Model (OCCAM) - Mohd. Fadzil Mohd Akhir, (Universiti Kebangsaan Malaysia, 2012)
The South China Sea (SCS) circulation in its southern region in the area between Peninsular Malaysia and East Malaysia was studied from the OCCAM (Ocean Circulation and Climate Advanced Modelling). This research aimed to illustrate the general overview of the seasonal surface current circulation and the surface temperature profile which are lacking in the region. The current along the Malaysia coast flows northward in the southwest monsoon and move in opposite direction in northeast monsoon with the maximum speed of 0.4 m/s and 1 m/s, respectively. While the current flows southward, the cooler water is transported into the region which reduces the temperature at the central of the basins nearly 3 °C. The study manages to analyse the importance of the monsoonal system on the region circulation and temperature distribution.